Securing Digital Trade: A Techno-Legal Analysis of E-Commerce Safeguards in Iraq’s Regulation No. 4/2025 - Mahmood Alaloosh; Ali Shaker Mahmood; Sabir Hussien Eliwy (Islamic Research Publiser, 2026)
This paper analyses the legal and technical protections created in accordance with the 2025 E-Commerce Regulation in Iraq and evaluates their compatibility with international regulations considering the swift changes in the digital trade landscape. It claims that the regulation offers a potentially strong legal framework for digital market regulation, but its success depends on its enforcement capacity and on sufficient technical and administrative infrastructure. In the absence of these conditions, the sector will be susceptible to fraud, breach of consumer data and tax evasion. The study methodologically uses doctrinal legal analysis of the regulation and its connection to existing domestic legislation, specifically the consumer protection law. This is supplemented by a well-organised comparative analysis of global data privacy and e-commerce regulatory frameworks, and a descriptive-analytical evaluation of the e-commerce situation in Iraq based on national reports and sectoral statistics. A techno-legal framework is used to assess data security, encryption, and the governance of digital identity. The results show that the regulation presents primary safeguarding measures, such as vendor licensing, transparency requirements, personal information protection, tax and customs supervision, and oversight through an electronic licensing platform. These controls demonstrate partial compliance with widely recognised consumer and data protection principles. Nonetheless, it faces challenges such as infrastructural constraints, the growth of informal online trade, and poor technical literacy among stakeholders. In terms of academics, this research study contributes to the discussion of digital regulatory capacity in less developed economies by incorporating both legal analysis and the technical compliance aspect. It reveals an absence of regulatory design and enforcement preparedness and serves as a platform for evaluating techno-legal governance of emerging digital markets.